2020
DOI: 10.1155/2020/2096834
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon for Dyes Removal: Modeling and Understanding the Adsorption Process

Abstract: Batch adsorption experiments have been conducted to investigate the removal of methyl orange from aqueous solution by an activated carbon prepared from prickly pear seed cake by phosphoric acid activation. The adsorption process has been described by using kinetic and isotherm models. The kinetic of adsorption was examined by pseudo-first-order, pseudo-second-order, and intraparticle diffusion models. Adsorption isotherm was modeled using Langmuir, Freundlich, Temkin and Dubinin–Radushkevich isotherms. The ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 58 publications
2
34
0
Order By: Relevance
“…Figure 10 shows that the current data fitswell in the pseudo-second order model due to its high value of correlation coefficient. The data are also supported by previous studies in which the removal of dyes was performed with prickly pear seed cakes [ 56 ].…”
Section: Resultssupporting
confidence: 88%
“…Figure 10 shows that the current data fitswell in the pseudo-second order model due to its high value of correlation coefficient. The data are also supported by previous studies in which the removal of dyes was performed with prickly pear seed cakes [ 56 ].…”
Section: Resultssupporting
confidence: 88%
“…is the binding constant related to the adsorption capacity and "n" is the adsorption intensity [90]. e surface heterogeneity or the adsorption capacity can be measured from 1/ n which ranges from 0 to 1. e lowest value of 1/n indicates the presence of more heterogeneity and multilayer adsorption [91]. Figure 13, elaborates the Freundlich isothermal plot (log q e vs. log C e ) for the adsorption of BGD on unmodified (R-TNP and R-CLP) and chemically modified with citric acid (CA-TNP and CA-CLP) adsorbents.…”
Section: Equilibrium Isothermal Studiesmentioning
confidence: 90%
“…From Figure 5, it can be observed that the filter material was able to capture about 218.233 mg of color per g of the filter material. In the literature, some other filter materials, such as activated carbon, have also been investigated for their potential adsorption capacity in terms of color; for instance, in a study conducted by El maguana et al [53] on the removal of dyes using activated carbon, it was observed that the material had an adsorption capacity of 336.12 mg/g at a pH of 7, which is slightly higher than the value obtained with natural zeolite in this study at pH values between 7.5 and 12.3.…”
Section: Adsorption Capacity Of the Filter Materialsmentioning
confidence: 99%